TO PARTICULARITY OF THE PHYSICAL DEVELOPMENT NEWBORN BORING FROM WOMEN WITH UNTILEKLAMPSHIA - More Olimova (Scholar Express Journals, 2025)
In work is described particularities of the factors anthropometria 100 newborn, been born from woman’s with untileklampshia (UE) depending on their postnatal gestation age, in compared aspect before 30 children, been born from woman’s without sign PE and extragenital of the diseases. It is done conclusion that amongst children, boring from women with untileklampshia, are concentrated unripe children (maturely and born prematurely), objective estimation which in early neonatal period imitated the clinic an hypocsyc-iscyemyc encephalopathia and its complications.
Keywords: newborn; unripe; untilereklampshia